PENGGUNAAN DAGING DAN TULANG IKAN BANDENG (Chanos chanos) PADA STIK IKAN SEBAGAI MAKANAN RINGAN BERKALSIUM DAN BERPROTEIN TINGGI - Fitri, Amiza; Anandito, R. Baskara Katri; Siswanti, Siswanti (Jurnal Teknologi Hasil Pertanian, 2016)
Milkfish (Chanos Chanos) was favored by many people and become one of the featured Fisheriescommodity. Processed fish product is very limited, especially, in the food industry as snack. Utilization of fishless than optimal because most only use meat and the bones is a waste. Bones milkfish is rich of mineral,especially calcium. Utilization of meat and bone fish is to optimize the utilization of fish on snack to improve thenutritional value. The experimental design use a complete randomized design (CRD) with one factors, namelythe use of three types of raw material milkfish include: meat milkfish, waste bones and whole milkfish. Step ofthis study were divided into two stages, the first stage is the stage of making a snack of fish sticks with differentbase materials, while the second step was to determine the chemical characteristics and the parameters werethe content of calcium, protein, fat, water, ash, carbohydrate and hedonic test. The whole part of milkfish, fishmeat, bones and head of milkfish was used as raw material on making sticks which was given effect onsuccessively increasing the content of protein and calcium. The chemical characteristic of the fish meat stickwas 23.89% of moisture content; 1.15% of ash content; 20.86% of fat content; 13.08% of protein content;61.030% of carbohydrates content; and 0.02% of calcium content. A fish bone stick in a row of 3.90%; 3.60%;24.18%; 8.99%; 59.16%; and 0.038%. A whole fish stick by 2.81%; 2.12%; 24.81%; 9.43%; 61.11%; and0.1923%. Due to the result of sensory evaluation on sticks hedonic scale of the whole fish sticks product werethe most preferred by panelist.